Полиязычное обучение через внедрение в учебно-воспитательный процесс междисциплинарной интеграции - Султанова, Г.Е. (My University, 2016)
The relevance. The goal. The method. The result. The conclusions. The concept of language policy of the Republic of Kazakhstan of the state language is determined by the Kazakh language, the Russian language as the main source of information on the different areas of science and technology as a means of the communication with the near and far abroad.However, the integration into the world economy is not possible without the knowledge of the world languages, especially English.Due to his intense study of the language situation for the majority of Kazakhstan people in full it can be designated as multilingual. That is the objective realities of today are formed in such a way that the Kazakhstan society is characterized with multilinguism.
Keywords: multilinguism; interdisciplinary integration